Phosphorus-nitrogen compounds. Part 56. Comparative syntheses and spectral properties of multiheterocyclic 2-cis-4-ansa and spiro-ferrocenyl (N/O)cyclotetraphosphazenes: Antituberculosis and antimicrobial activity and DNA interaction studies. (2nd January 2022) - Binici, Arzu; Okumuş, Aytuğ; Yakut, Mehtap; Elmas, Gamze; Kılıç, Zeynel; Koyunoğlu, Dila; Açık, Leyla; Şimşek, Hülya
Abstract: In the present study, two types of starting compounds; hexachloro(N/O)-cyclotetraphosphazenes containing mono-ferrocenyl-pendant arm, namely, mono-ferrocenyl-2- cis -4-dichloro-ansa-(2, 4-ansa; 2 ) and mono-ferrocenyl-spiro-(spiro; 3 ) were prepared by the reaction of N4 P4 Cl8 (1 ) with sodium 3-( N- ferrocenylmethylamino)-1-propanoxide (L ). Reactions of 2, 4-ansa (2 ) with excess benzylamine and n- hexylamine resulted in the formation of partly substituted 2- cis -4-dichloro-ansa-cyclotetraphosphazenes (2a and 2b ). In contrast, spiro (3 ) gave fully substituted mono-ferrocenyl-spiro-cyclotetraphosphazenes (3a and 3b ) with excess benzylamine and n-hexylamine. As expected, the 2, 4-ansa cyclotetraphosphazenes (2, 2a, and 2b ) have two distinct stereogenic P-centers. The structures of cyclotetraphosphazenes were evaluated by elemental analysis, ESI-MS, FTIR, 1 H, 13 C, and 31 P-NMR techniques. The antibacterial and antifungal activities against some selected bacteria and yeast strains, antituberculosis activities against Mycobacterium tuberculosis H37Rv, and DNA cleavage activities of mono-ferrocenyl-cyclotetraphosphazenes were also discussed. Compounds 2b, 3a, and 3b exhibited antifungal activity against C. albicans (MIC= 156.3 µM) higher than reference antibiotic Ketoconazole. Moreover, four compounds displayed antituberculosis activity against the M. tuberculosis H37RV. Compound 2a (20 μg/mL) is the most potent of the four compounds. Graphical abstract: UF0001